The Phenomenon of Legal Exception in Indonesian Legal Pluralism: - Soi, Andi Bahri; Murdan, Murdan (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The legal exception in the study of legal pluralism revealed in this article is not in the context of procedural law. This study highlighted the use of “exception” term. Legal exception is defined as an exception or not included in one carriage of legal reasoning. Through the judge's court decision No. 089/Pdt.G/2010/PA.GM on the Application for Polygyny Permit. Purpose: This paper aimed to explore and analyze the legal exceptions on plurality legal context of Indonesia related to the issue of hypersexuality and gender justice in polygyny case of Sasaknese Muslim Mariage in Lombok West Nusa Tenggara. Methods: A qualitative normative approach is employed; departing from the legal facts spesifically in Giri Menang Religious Court, the analysis and discussion applyed in this paper are the reasoning, paradigm, approach, and flow of socio-legal studies in law and society issue. Results: The findings indicated that the partiality of the judge's reasoning by ignoring the term legal exception in the context of legal pluralism. The judge's decision on the polygamy permit was not based on real legal rationality, but due to the applicant experienced by hyper sexuality. The odd thing of judge's reasoning only considers State Law and Religion, and ignores the Customary Law of Sasak marriage. While the Indonesian marriage law, there is no law that permits a husband to engage in polygamy based on the hypersexuality or other suffers deseases of husband. However, the law allows a husband to be polygamous on the basis of an incurable disease of the wife. Implication: The serious implication of this study espoused the distortion of the existence of customary law due to the strongest hegemony of state and religious law. Therefore various further studies are needed to reveal the relevance of customary law to positive law in Indonesia. Originality: The novelty presented in this article are the response of religious court judges to the existence of legal plurality in Indonesia, namely State Law, Religious Law, and Customary Law. The court decision emphasized that judges obey only for state and religious law, and ignored for the customary law. Even though the legal plurality of Indonesian society is directly protected by the constitution